Pendidikan Karakter Sosial Melalui Kegiatan Ekstrakurikuler di Pondok Pesantren Al-Islam Joresan Ponorogo - Muhamad Ridwan (Excelencia: Journal of Islamic Education & Management, 2024)
This research is motivated by the decline in the social character of santri living in Islamic boarding schools, such as the fading culture of mutual cooperation and the low level of concern among santri towards other friends. This reality is a problem that needs to be researched and a solution found, because Islamic boarding schools are Islamic educational institutions that emphasize the formation of noble character. Based on initial data exploration, researchers found that there was social character education through extracurricular activities at the Al-Islam Islamic Boarding School Joresan Ponorogo. This research aims to describe the forms of activities carried out to shape the social character of santri, the values ​​of multicultural education contained in these activities, and their positive impact in shaping the social character of santri. The research method used in this research is qualitative research using an ethnographic approach. Data collection techniques used include interview techniques, observation and documentation. Data analysis used in this research includes data collection, condensation, data presentation and conclusion drawing. The results of this research found that: (1) the activities carried out to shape the social character of students were through Muhaḍarah and Scout activities which used a supplement model; (2) these activities contain the values ​​of multicultural education in the form of equality, justice, pluralism and democracy; (3) the implementation of Muhaḍarah and Scout activities has a positive impact on the formation of the social character of students.